2011
DOI: 10.1097/mat.0b013e31823b9692
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Generating Silicone As a Blood-Contacting Biomaterial

Abstract: Coagulation upon blood-contacting biomaterials remains a problem for short and long-term clinical applications. This study examined the ability of copper(II)-doped silicone surfaces to generate nitric oxide (NO) and locally inhibit coagulation. Silicone was doped with 3-micron copper (Cu(0)) particles yielding 3 to 10 weight percent (wt%) Cu in 70-μm thick Cu/Silicone polymeric matrix composites (Cu/Si PMCs). At 3, 5, 8 and 10 wt% Cu doping, the surface expression of Cu was 12.1 ± 2.8%, 19.7 ± 5.4%, 29.0 ± 3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Therefore, as the same amount of Cu (10 wt% of Cu/polymer matrix) was added to fibers and to tubing, both surfaces had similar catalytic activity on NO donors and thus similar rate of NO release per unit area. Previous 10 wt% surfaces with either 3 μm [19] and 50 nm [21] copper particles produced 9 × 10 −10 and 15 × 10 −10 mol cm −2 min −1 , respectively, under identical in vitro conditions. Due to the NO flux, the NOgen ECC lungs were less thrombogenic than their non NOgen controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, as the same amount of Cu (10 wt% of Cu/polymer matrix) was added to fibers and to tubing, both surfaces had similar catalytic activity on NO donors and thus similar rate of NO release per unit area. Previous 10 wt% surfaces with either 3 μm [19] and 50 nm [21] copper particles produced 9 × 10 −10 and 15 × 10 −10 mol cm −2 min −1 , respectively, under identical in vitro conditions. Due to the NO flux, the NOgen ECC lungs were less thrombogenic than their non NOgen controls.…”
Section: Discussionmentioning
confidence: 99%
“…The NOgen shunts were coated tip-to-tip with either the two-part silicone or with10 wt% of 50 nm Cu(II) oxide particles (Sigma Aldrich, St Louis MO, Product number 544868) in tygon polymer. NO-gen silicone was used to coat the angiocaths and connectors in either silicone using the synthesis procedure described previously [19]. To coat tubing, tygon pellets chopped up from tygon tubing were dissolved in tetrahydrofuran (THF) (Sigma Aldrich, St Louis MO) at, using 1g pellets per 3mL THF by vortexing the mixture for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copper‐containing materials such as polyurethane loaded with copper nanoparticles can also continuously generate nitric oxide by the catalytic decomposition of blood RSNO . Amoako et al have reported that Cu‐mediated NO‐generating silicone has the ability to catalyze nitric oxide formation and reduce blood coagulation . Cu–SNAP composites, fabricated by incorporating copper nanoparticles onto the SNAP films, provide controlled NO release and reduced platelet adhesion .…”
Section: Introductionmentioning
confidence: 99%